Building a New South Africa : One Conversation at a Time - Thelen, David; Morgan, Karie L. (Book collections on Project MUSE., 2015)
Once a thriving, multiracial community, the Sophiatown suburb of Johannesburg was home to many famous artists, musicians, and poets. It was also a place where residential apartheid was first put into practice with forced removals, buildings bulldozed, and the construction of new, cheap housing for white public employees. David Thelen and Karie L. Morgan facilitate conversations among today's Sophiatown residents about how they share spaces, experiences, and values to raise and educate their children, earn a living, overcome crime, and shape their community for the good of all. As residents reflect on the past and the challenges they face in the future, they begin to work together to create a rich, diverse, safe, and welcoming post-Mandela South Africa.